Photocatalytic and adsorptive performance of polyvinyl alcohol/chitosan/TiO2 composite for antibiotics removal: single- and multi-pollutant conditions. (6th August 2022) - N, Neghi; Kumar, Mathava
Abstract: A polymer-TiO2 macro composite (i.e., PVA-CS-TiO2 ) was synthesized via chemical precipitation of PVA-CS-TiO2 blend in alkali/solvent medium and applied for the removal of three model antibiotics (i.e., metronidazole (MNZ), ceftiofur (CEF) and tetracycline (TET)), as single compound and multi-compound conditions. The photocatalytic and adsorptive removals of antibiotics (concentrations of 0.1, 1 and 10 mg L −1 ) by the composite in an UV reactor system (32 W UV-C power, 0.3 g L −1 of composite) was assessed through kinetic models. Antibiotics adsorption followed pseudo-second-order kinetics, and the order of adsorption was MNZ > TET > CEF. On the other hand, the hydrophilic MNZ was degraded faster compared to hydrophobic CEF and TET drugs. Moreover, UV reactor system exhibited antagonistic behavior under multi-compound condition. Micro-toxicity of antibiotics was performed using bioluminescent bacterium Vibrio fischeri and EC50 of CEF, TET and MNZ were found to be 18.25 mg L −1, 173.8 mg L −1, and 668.6 mg L −1, respectively. However, the relative toxicity levels of PVA-CS-TiO2 and treated effluent were well with the limits as inferred from the microtoxicity analysis. Thus, synthesized biocompatible composite exhibited structural stability, consistent performance for three photocatalytic cycles for all antibiotics at a minimal catalyst loading, easily retained using metallic tea strainer and does not exhibit microtoxicity has a scope for real-time applications. HIGHLIGHTS: PVA-CS-TiO2 was stable and produced good antibiotics removal under single and multi-compound conditions. Removal rates of antibiotics by adsorption and photocatalysis were modelled. Hydrophilic MNZ exhibited faster degradation than hydrophobic CEF and TET. EC50 of antibiotics was determined using Vibrio fischeri bacterium. Hydrophobic antibiotic exhibited greater toxicity to V. fischeri . Graphical Abstract